A prática pedagógica intercultural do/a professor/a Munduruku - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This work will focus on intercultural pedagogical practice of / the teacher / the Munduruku in the State School boiler Esther Cardoso, located at Kwata community of Indigenous Kwata- Orangery Municipality of Borba / Am. It is mainly aimed to "identify and analyze the pedagogical practice of / the teacher / the Munduruku of elementary school final years, the indigenous school Kwata community and its relationship with the cultural elements Munduruku". Initially, we tried to identify the cultural elements of the Munduruku people and check the intercultural pedagogic practice / a teacher / a community school. The work was developed through a case study that used as data collection technique: The observation, semistructured interviews and document analysis. The data collected were given a qualitative approach. From the dialogues between the objectives outlined, the data collected and foundational theories, we got the following considerations: Some / the teacher / the Munduruku need to better understand what is and what is the meaning of intercultural education. Such a claim derives from the fact that most / the teacher / the show understand and, where possible, promote a dialogue between disciplines and cultural elements present in the community. There are those / those who are content to identify and name a classroom, stereotyped cultural aspects of Munduruku people, that is, are content to relate the cultural elements as an "object" or "accessory" and this may prevent the real aspects cultural that are "alive" in the reality of Kwata community are seen and seized. This practice, which can be identified as relational intercultural teaching practice does not answer, in our opinion, the expectations of / the own / the teachers / as, of leaders and community / as in general
Keywords: Educação Intercultural; Prática Pedagógica; Intercultural Education; Teaching Practice; CIÊNCIAS HUMANAS: EDUCAÇÃO: ENSINO-APRENDIZAGEM: MÉTODOS E TÉCNICAS DE ENSINO